Evaluation of the contemporary cultural landscape based on multi-dimensional value coupling: Case study on the Grand Canal, Hangzhou section - Wenli Dong; Wenying Han; Yue Xu; Jiwu Wang (PLoS ONE, 2025)
In the context of building the Grand Canal National Cultural Park, the heritage conservation of the Grand Canal has entered a new stage since its inscription as a World Heritage site. Scientifically evaluating the value of various cultural landscape projects along the Grand Canal is the fundamental basis for coordinating the conservation of the Grand Canal’s World Heritage sites, land use control, and urban development construction. Based on the research on the evolution of cultural landscape value paradigm, the multi-dimensional value evaluation system of the Grand Canal cultural landscape is constructed. Based on the coupling coordination degree theory, the synergistic adjustment mechanism of the conservative value and developmental value system of the canal cultural landscape is explored. The value evaluation of the 10 contemporary cultural landscape projects implemented since the application of the Grand Canal in Hangzhou is carried out, and the coupling coordination of their conservation and utilization is analyzed. The cultural landscape conservation and utilization mode of the Grand Canal in Hangzhou is discussed, which provides a reference for the cultural landscape construction along the “city-river interdependence” Grand Canal.